Pendampingan Pemasaran Jagung Astan Berbasis Digitalisasi Pada UD. Beriuk Maju Barat - Armiani; Rusli Amrul; Faizatul Fajariah; I Nengah Arsana; Nendy Pratama Agusfianto; Satriawan (Valid Jurnal Pengabdian, 2024)
Digital-based marketing assistance for Astan Corn at UD. Beriuk Maju, Jagagaraga Village, West Lombok is an implementation of community service carried out by STIE AMM Mataram lecturers. This assistance is in order to increase the group's understanding of the problems that arise in carrying out the Astan Corn business. The problem that arises during mentoring is that the development of the Astan Corn business does not yet have a clear plan so that the goals and objectives of the Astan Corn business to be achieved are not clear, there is no marketing promotion using digitization and there is a lack of access to collaborate or in the form of cooperation with other parties. The method of implementing this service uses counseling and mentoring for business groups. The result obtained from this service is that the group understands business management. The group understands marketing using digitization and the group will try to collaborate with other parties to develop the astan corn business.